Diversity and evolution of bacterial bioluminescence genes in the global ocean. Issue 2 (14th March 2020) - Vannier, Thomas; Hingamp, Pascal; Turrel, Floriane; Tanet, Lisa; Lescot, Magali; Timsit, Youri
Abstract: Although bioluminescent bacteria are the most abundant and widely distributed of all light-emitting organisms, the biological role and evolutionary history of bacterial luminescence are still shrouded in mystery. Bioluminescence has so far been observed in the genomes of three families of Gammaproteobacteria in the form of canonical lux operons that adopt the CDAB(F)E(G) gene order. LuxA and luxB encode the two subunits of bacterial luciferase responsible for light-emission. Our deep exploration of public marine environmental databases considerably expands this view by providing a catalog of new lux homolog sequences, including 401 previously unknown luciferase-related genes. It also reveals a broader diversity of the lux operon organization, which we observed in previously undescribed configurations such as CEDA, CAED and AxxCE. This expanded operon diversity provides clues for deciphering lux operon evolution and propagation within the bacterial domain. Leveraging quantitative tracking of marine bacterial genes afforded by planetary scale metagenomic sampling, our study also reveals that the novel lux genes and operons described herein are more abundant in the global ocean than the canonical CDAB(F)E(G) operon.